THE INFLUENCE OF SEA SURFACE TEMPERATURE ON THE CATCHES SKIPJACK (Katsuwonus pelamis) IN THE PORT OF LAMPULO BANDA ACEH - Khaidir Ali; T. Ersti Yulika Sari; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aim of this research is to know the influence of sea surface temperatureon the catches skipjack (Katsuwonus pelamis) in the port of Lampulo Banda Aceh.This research was doing during June 22th 2015 – July 5th 2015 in the waterworksaround Lampulo Banda Aceh port. This research used servey method. This fieldsurvey shows that the average of temperature’s sea level at 3 stations were 29,16oC.Temperature’s sea level by used Citra Aqua MODIS was around 29.4oC-29.8oC andThe high temperature during 2011-2013 used temporal’s temperature was around28oC-28.3oC on west season. According to spasial assessment, the most sea surfacetemperature was 30.04oC-30.58o.C which spread around March-August at decidedstations. The lowest amount of fish catching (102.806 Kg) was on 2010 February andThe highest amount (574.167 Kg) on 2014 November. This research shows that seasurface temperature according to spasial and temporal was influenced skipjack fishcatching at Lampulo Banda Aceh Port. The potential of sea surface temperature forcatch skipjack fish at Lampulo Banda Aceh Port is 28oC-29oC on transition east-westseason. The Fluctuation of skipjack fish catching based on wind season shows thatwest season was the lowest amount of fish catching while transition east-west seasonand east season is equal to the amount of fish catching. East season was the mostamount of skipjack fish catching while transition east-west season was the higestamount of skipjack fish catching.Keywords: Sea Surface Temperature, Skipjack, Lampulo Port